A collection of genetically engineered Populus trees reveals wood biomass traits that predict glucose yield from enzymatic hydrolysis. Issue 1 (December 2017) - Escamez, Sacha; Latha Gandla, Madhavi; Derba-Maceluch, Marta; Lundqvist, Sven-Olof; Mellerowicz, Ewa; Jönsson, Leif; Tuominen, Hannele
Abstract Wood represents a promising source of sugars to produce bio-based renewables, including biofuels. However, breaking down lignocellulose requires costly pretreatments because lignocellulose is recalcitrant to enzymatic saccharification. Increasing saccharification potential would greatly contribute to make wood a competitive alternative to petroleum, but this requires improving wood properties. To identify wood biomass traits associated with saccharification, we analyzed a total of 65 traits related to wood chemistry, anatomy and structure, biomass production and saccharification in 40 genetically engineeredPopulus tree lines. These lines exhibited broad variation in quantitative traits, allowing for multivariate analyses and mathematical modeling. Modeling revealed that seven wood biomass traits associated in a predictive manner with saccharification of glucose after pretreatment. Four of these seven traits were also negatively associated with biomass production, suggesting a trade-off between saccharification potential and total biomass, which has previously been observed to offset the overall sugar yield from whole trees. We therefore estimated the "total-wood glucose yield" (TWG) from whole trees and found 22 biomass traits predictive of TWG after pretreatment. Both saccharification and TWG were associated with low abundant, often overlooked matrix polysaccharides such as arabinose and rhamnose which possibly represent new markers for improvedPopulus feedstocks.